Towards a socially legitimate ethical review of animal research: advancing the field of 'public engagement with ethics' - Salter, Kathleen H. (2025)
The emergence of a 'participatory turn' in the sociological study of science and technology reflects a growing recognition of the value of diverse 'non-expert' perspectives in shaping and overseeing research agendas. The interdisciplinary field of Science and Technology Studies (STS) has been instrumental in laying the theoretical groundwork and driving the methodological advances necessary for translating this aim to the policy sphere. Building on this momentum, there is a nascent push within STS to expand its focus to incorporate institutional ethical frameworks, aiming to develop a field of ‘Public Engagement with Ethics’. Central to these efforts is the need to reconsider the evolving role of ‘expertise’ within, and public expectations of these structures to ensure their social legitimacy – an area that has received surprisingly limited attention so far. This thesis responds to such calls by examining the specific context of UK Animal Research and Ethical Review Bodies (AWERBs), which serve as ‘in-house’ ethics committees responsible for overseeing all research involving live animals within research institutions. This case is particularly compelling due to the complex historical interactions between “the public” and animal research. These interactions have resulted in a policy context characterised by regulatory secrecy, driven by concerns about animal rights activism and researcher safety, and an outdated reliance on reductive opinion polling to gauge the legitimacy of animal research practice and regulation. Recognising the theoretical and methodological complexities of engaging lay publics on the topic of ethical review, this thesis introduces a novel concept - 'Imaginaries of Ethics'. This conceptual framework offers a productive approach to explore and conceptualise the ‘ideal’ ethical review process, as well as the underlying visions of animal research futures that these imaginaries embody. The effectiveness of this approach is demonstrated through policy analysis, examining 15 AWERB policy and guidance documents, and through public engagement, conducted with six online focus groups involving 28 lay participants. The analyses presented indicate a significant disparity between the expert-driven scientific rationality guiding AWERB protocols and the more embodied, political, and contextual ethics envisioned by lay participants. While participants did not foresee themselves actively engaging in AWERB negotiations, they valued the prospect of “upstream” exploratory ethical dialogues. However, the current AWERB ethical review process remains largely “downstream”, taking place late in research design and focusing on scientific/welfare risks within a structured timeframe using a Utilitarian harm/benefit assessment. This misalignment highlights a lack of social legitimacy in the UK’s regulatory approach to animal research, which ostensibly favours traditional science paradigms and views publics as problematic observers. This thesis, therefore, concludes that AWERBs must embrace the political and emotional dimensions of ‘ethics’, moving beyond a focus on established expertise and objectivity. Implementing practical measures such as fostering a Culture of Care within the committee, improving transparency, and nurturing reflective practices among members could better align institutional ethical review with public expectations, enhancing the social legitimacy of animal research regulation in the short term. Meanwhile, more social science research on how publics engage with ‘ethics’ can drive future shifts towards more robust ethical review systems and, consequently, truly responsible research.